PEER COUNSELING TRAINING AS A METHOD OF SEXUAL HEALTH PROMOTION IN ADOLESCENTS - Khoiriyah Isni (Universitas Airlangga, 2021)
ABSTRACT One characteristic of adolescents is their tendency to share information, tell stories, and gather with their peers. They may experience the negative effects of these habits when they do not have adequate life skills, especially in terms of sexuality. On the other hand, these activities present an opportunity for health promotion through peer-based approaches or peer counseling. The goal is to know the effects of peer counseling methods as media of information to increase adolescents’ knowledge and attitude regarding sexual problems. The study used a quasi-experimental approach with a nonequivalent control group design. The sample consisted of 17 respondents between 15-24 years old living in Banguntapan, Bantul, Yogyakarta who fulfilled the inclusion and exclusion criteria. Data were collected with the purposive sampling technique. The research instrument used was a questionnaire. The results showed that there was a difference in the average knowledge level (p = 0.021) and attitudes (p = 0.000) of respondents related to sexuality before and after receiving peer counseling training. Methods and media used in delivering health information to adolescents should be diversified in schools, in the community, and in health services to generate interest in accessing and heeding appropriate health information. Keywords: peer counseling, sexuality, adolescents, health promotion